(untitled) (International Journal of Advanced Research in Computer Science, 2017)
In this paper, a new method of optimization is proposed based on the combination of Ant Colony Optimization (ACO) and Chaos Theory to solve Dynamic Travelling Salesman Problem (DTSP). ACO algorithm has been modified in a way by using chaos theory to obtain an optimal solution to solve DTSP. By combination of both chaos theory and ACO algorithm, a hybrid algorithm is created which provided a better net to solve DTSP. In hybrid algorithm, pheromone updating rule is performed by using Logistic Map function and is non-linear which can prevent premature convergence. Features such as high precision and good convergence rate to reach best results indicate our proposed hybrid algorithm is better. Â Keywords: Dynamic Travelling Salesman Problem (DTSP); ACO; chaos theory; logistic map function; hybrid algorithm